A multi-responsive organogel and colloid based on the self-assembly of a Ag(i)-azopyridine coordination polymer. Issue 13 (5th March 2021) - Li, Botian; Xiao, Da; Gai, Xiaodong; Yan, Bo; Ye, Haimu; Tang, Liming; Zhou, Qiong
Abstract : A multi-responsive self-healable organogel and colloid were fabricated by the assembly of a coordination polymer derived from Ag(i ) and azopyridine ligands. Abstract : In this work, through the coordination of C 3 symmetric azopyridine ligands and Ag(i ), coordination polymers with azo groups on the main chain were prepared. The trans coordination polymer formed an organogel with a network of nanofibers at low critical gelation concentrations, and it exhibited the abilities of self-healing and multi-stimuli response to heating, light, mechanical shearing, and chemicals due to the presence of dynamic coordinating bonds. On the other hand, the cis coordination polymer was found to assemble into nanoparticles to give a responsive colloid, which can produce fibrous precipitation in several days upon visible light irradiation due to the isomerization of the azo groups. This work provides a novel example for the design of a multi-responsive organogel and colloid based on the structural transformation of coordination polymers.